Characterizing upper limb function in the context of activities of daily living in CLN3 disease. Issue 5 (8th February 2021) - Hildenbrand, Hanna; Wickstrom, Jordan; Parks, Rebecca; Zampieri, Cris; Nguyen, Thuy‐Tien; Thurm, Audrey; Jenkins, Kisha; Alter, Katharine E.; Matsubara, Jesse; Hammond, Dylan; Soldatos, Ariane; Porter, Forbes D.; et al.
Abstract: In CLN3 disease, impairments in motor function are frequently reported to have later onset compared to visual and cognitive decline, but upper limb motor function has yet to be explored in this population. In a cohort of 22 individuals with CLN3, we used a novel application of multiple measures to (1) characterize motor function, particularly of the upper limbs, in activities of daily living (ADLs), and (2) explore associations between motor function and age as well as visual ability, disease severity, and cognitive function, as evaluated by the Unified Batten Disease Rating Scale (UBDRS), a validated CLN3 disease measure. ADLs that required coordination, speed, and fine motor control were particularly challenging for children with CLN3 based on item‐level performance across direct assessments (Jebsen–Taylor Hand Function Test [JTHFT] and MyoSet Tools) and caregiver reports (Pediatric Evaluation of Disability Inventory‐Computer Adaptive Testing [PEDI‐CAT] and Patient‐Reported Outcomes Measurement Information System [PROMIS] Pediatric Upper Extremity). Poorer visual ability, disease severity, and cognitive function were associated with worse performance on these measures, whereas age had limited impact. These findings support the need for children with CLN3 to receive skilled clinical evaluation and treatment tailored to their individual needs, particularly in the context of ADLs, as their symptom profile progresses.